Kecenderungan impulsive buying produk kecantikan: Bagaimana persepsi pengguna media sosial terhadap beauty influencer? - Maria Yosefina Johan; Sahat Saragih; Sayidah Aulia Ul Haque (INNER: Journal of Psychological Research, 2023)
Abstract Impulsive buying has become a significant phenomenon in the consumer world today. In the context of the beauty industry, impulsive buying of beauty products is increasingly widespread, especially among social media users. One of the factors influencing impulsive buying behavior is the perception of beauty influencers. Therefore, this study aims to explore the relationship between the perception of beauty influencers and the tendency for impulsive buying of beauty products among social media users. This research uses the Pearson product-moment analysis technique to determine the relationship between perception of beauty influencers and impulsive buying tendencies with 100 subjects as respondents. The results of this study show that the higher someone’s perception of beauty influencers, the higher the tendency for impulsive buying among social media users, and vice versa, the lower someone’s perception of beauty influencers, the lower the tendency for impulsive buying among social media users. Keywords: Impulsive Buying, Beauty Influencer, Perception